Breakdown characteristic analysis of paper- oil insulation under AC and DC voltage - Anuar, N. F.; M. Jamail, N. A.; A. Rahman, R.; Kamarudin, M. S. (2012)
This paper presents the study of breakdown characteristic of Kraft paper insulated with two different types of insulating fluid, which are Palm oil and Coconut oil. Palm oil and Coconut oil are chosen as the alternative fluid to the transformer oil because it has high potential and environmentally-friendly. The Segezha Kraft papers with various thicknesses (65.5 gsm, 75 gsm, 85gsm, 90 gsm) have been used in this research. High Voltage Direct Current (HVDC), High Voltage Alternating Current (HVAC) and carbon track and severity analysis is conducted to observe the sample of aging Kraft paper. These samples have been immersed using Palm oil and Coconut oil up to 90 days to observe the absorption rate. All samples started to reach saturation level at 70 days of immersion. HVDC and HVAC breakdown experiments have been done after the samples had reached the saturation level based on normal condition, immersed in Palm oil and immersed in Coconut oil. All samples immersed in liquid show different breakdown voltage reading compared to normal condition. The analysis of carbon track and severity on surface has been done using Analytical Scanning Electron Microscope (SEM) Analysis. The results of the experiment show that the sample of Kraft paper immersed in Palm oil was better than Coconut oil immersed sample. Therefore the sample condition was the main factor that determines the value of breakdown voltage test. Introduction